Co‐expression of march5b and tlr7 in large yellow croaker Larimichthys crocea in response to Cryptocaryon irritans infection. Issue 2 (14th July 2015) - Zhang, D. L.; Yu, D. H.; Chen, J.; Chen, C.; Wang, Z. Y.
<x xml:space="preserve">Abstract</x> In this study, molecular characteristics of march5b and co‐expression of march5b and tlr7 in response to the infection of Cryptocaryon irritans in the large yellow croaker Larimichthys crocea were investigated. The full‐length complementary (c)DNA of march5b was 1314 bp, including an open reading frame of 846 bp encoding a polypeptide of 281 amino acids, and the full‐length genomic sequence was composed of 23 577 nucleotides, including six exons and five introns. The putative March5b protein contained a RINGv motif and four transmembrane domains. The march5b transcripts were broadly distributed in all detected tissues, with a strong expression in blood, brain and gills, and a weak expression in kidney by quantitative PCR analysis. The expression of march5b and tlr7 in the skin, gills, spleen and head kidney changed in the same manner at most time points post‐primary infection with C. irritans. Significant increase was observed in the skin with march5b at days 2 and 3 by 26·10 and 6·88 fold, respectively, and with tlr7 at day 3 by 57·68 fold, when compared with the control. Their expressions, however, were decreased in the gills, especially at day 3 (march5b by 8·9%, tlr7 by 22·06%). In the spleen and head kidney, march5b and tlr7 transcripts were up‐regulated early, then noticeably declined at day 3. These results suggested that march5b and tlr7 are co‐expressed in response to parasite infection and March5b probably catalyses ubiquitination of some proteins of TLR7 signalling pathway.